Electrical Palestine: Capital and Technology from Empire to Nation, Fredrik Meiton (2019) Waste Siege: The Life of Infrastructure in Palestine, Sophia Stamatopoulou-Robbins (2019). (1st January 2022) - Banko, Lauren
Review of: Electrical Palestine: Capital and Technology from Empire to Nation, Fredrik Meiton (2019)Oakland: University of California Press, 305 pp., 9 b&w illus., 2 maps, 3 tables, ISBN: 9780520295889 (cloth), $85ISBN: 9780520295896 (paperback), $29.95Waste Siege: The Life of Infrastructure in Palestine, Sophia Stamatopoulou-Robbins (2019)Stanford: Stanford University Press, 313 pp., 15 b&w illus., 1 map, ISBN: 9781503610897 (paperback), $28